2017
DOI: 10.1002/ejic.201700795
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Synthesis of Three Compounds Featuring the [Ge4S10]4– Anion from a Water‐Soluble Thiogermanate Precursor

Abstract: Applying a new synthetic approach in which transition metal complexes and a thiogermanate source are in different liquid phases resulted in crystallization of three new compounds with the adamantane-like [Ge 4 S 10 ] 4anion at room temperature. In the crystal structure of [Ni(cyclam)] 3 [Ni-(cyclam)(H 2 O) 2 ][Ge 4 S 10 ] 2 ·21H 2 O (I, cyclam = 1,4,8,11-tetraazacyclotetradecane), the two different Ni 2+ -centered complexes and two unique [Ge 4 S 10 ] 4anions are joined by H-bonding interactions with a water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 124 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…In a unique synthetic approach, it was also shown that those clusters can be made electrochemically using a Sn2Se3 cathode in a [Et4N]Br electrolyte solution in ethane-1,2-diamine to form [Et4N]4[Sn4Se10] (517) [283] The known Ge4E10 cluster compounds are often used as reactants in ion exchange reactions (method L) to introduce a desired functionality or structural template to the compound, such as larger ammonium cations forming lamellar structures (521-538), [284][285][286] organic molecules (539-546) [287][288][289][290][291] or transition metal complexes with interesting optical properties(547-551). [289,292,293] The family of clusters with metal complex counterions could also be expanded by starting from elements and binary precursors in solvothermal reactions (method B) to not only obtain more Ge clusters (552-556), [294][295][296][297] but also Sn congeners as well as rare earth containing examples(557-562). [298][299][300] In one case, the addition of antimony to such a reaction mix of GeO2 and elemental sulfur led to the formation of a compound with two distinct clusters, [(Me)2NH2]6[Ge2Sb2S7][Ge4S10] (563), one adamantane-type and another ternary molecule with noradamantane like topology.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…In a unique synthetic approach, it was also shown that those clusters can be made electrochemically using a Sn2Se3 cathode in a [Et4N]Br electrolyte solution in ethane-1,2-diamine to form [Et4N]4[Sn4Se10] (517) [283] The known Ge4E10 cluster compounds are often used as reactants in ion exchange reactions (method L) to introduce a desired functionality or structural template to the compound, such as larger ammonium cations forming lamellar structures (521-538), [284][285][286] organic molecules (539-546) [287][288][289][290][291] or transition metal complexes with interesting optical properties(547-551). [289,292,293] The family of clusters with metal complex counterions could also be expanded by starting from elements and binary precursors in solvothermal reactions (method B) to not only obtain more Ge clusters (552-556), [294][295][296][297] but also Sn congeners as well as rare earth containing examples(557-562). [298][299][300] In one case, the addition of antimony to such a reaction mix of GeO2 and elemental sulfur led to the formation of a compound with two distinct clusters, [(Me)2NH2]6[Ge2Sb2S7][Ge4S10] (563), one adamantane-type and another ternary molecule with noradamantane like topology.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%